Mixed-methods evaluation of integrating female genital schistosomiasis management within primary healthcare: a pilot intervention in Ogun State, Nigeria. (24th March 2023) - Piotrowski, Helen; Oluwole, Akinola; Fapohunda, Victoria O; Adejobi, Josephine B; Nebe, Obiageli J; Soneye, Islamiat; Kafil-Emiola, Maryam; Gideon, Ntuen Uduak; Ekpo, Uwem F; Ahmed, Aminat O; Abdussalam, Hameedat Opeyemi; Imhonopi, Gloria B; et al.
Abstract: Background: Detection and management of female genital schistosomiasis (FGS) within primary healthcare is crucial for achieving schistosomiasis elimination, however, current technical strategies are not feasible in many settings. In Nigeria, there are currently no established standard operating procedures to support front-line health workers. This article presents an evaluation of piloting an FGS care package in two LGAs of Ogun State, Nigeria. Methods: We used quantitative and qualitative analysis, including 46 interviews with patients, health workers and the quality improvement team; observations of training, learning sessions and supervision across 23 heath facilities; and records of patients detected and managed. Results: Of 79 women and girls who were screened, 66 were treated and followed up. Health workers assimilated knowledge of FGS and effectively diagnosed and managed patients, demonstrating the feasibility of using symptomatic screening and treatment tools to diagnose and care for women or girls with suspected FGS. Challenges included establishing a referral pathway to tertiary care for patients with complications, insecurity, gender norms that limited uptake and sensitization, the limited capacity of the workforce, conflicting priorities and praziquantel acquisition. Conclusions: Simple tools can be used in primary healthcare settings to detect and manage women and girls with FGS. Contextual challenges must be addressed. Sustainability will require political and financial commitments.